Configurations of Earth's magnetosphere in response to variations in z component Solar-wind flow during the southward IMF. (17th November 2020) - Li, Lingjie
Abstract: Based on the compressible resistive MHD models, the Earth's dipole magnetic field is employed to investigate magnetic reconnection driven by the solar wind with southward interplanetary magnetic field. By including the z- component solar wind velocity v swz in a three-dimensional compressible global resistive MHD simulation with uniform resistivity, we found that v swz does not affect the location of magnetic reconnection on the dayside magnetopause in the interaction of southward magnetic field of the solar wind with the Earth's dipole field. However, significant deviation of the central plasma sheet in the magnetotail from equatorial plane can occur. Detailed study also shows that v swz promotes magnetic reconnection at the dayside magnetopause, and the reconnection rate and deviation of magnetotail current sheet both increase with v swz . In particular, the deviation angle increases linearly with v swz . The results here can be useful for understanding observed substorm behavior in the magnetosphere.